The Effect of Drilling Technique on Students’ Writing Skills in Composing Recount Text - Zamroni (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2025)
Composing recount text ideally conducted with cues instead of freely. At school, students have less time allocation for writing. These were the reason to conduct the research entitled; The Effect of Drilling Technique on Students’ Writing Skills in Composing Recount Text. The aim of this research were; 1. Found out the effect of drilling technique on students’ writing skill in composing recount text; 2. Foound out how the students perceive of drilling technique as a mean to help them in composing recount text. This research was conducted with quantitative and qualitative method at once or called mixed method. The quantitative data collection techniques are pre-test and post-test. the qualitative data collection technique was interview. The quantitative data analysis technique was paired sample t-test. The qualitative data analysis was Miles and Huberman technique. Based on the paired sample statisticts, the sig (two tailed) les than the α (significant level) (0.000 < 0.05), so drilling technique affected the students’ writing skill in composing recount text.  The qualitative data showed that students’ considered drilling technique as a teaching technique which help them composing recount text; Two factors encourages this consideration of the students about drilling technique, those are: 1) Drilling technique used example in the learning and teaching process before the students were enhancing into the practice; and 2) Drilling technique used repetitions within the teaching and learning process, so the students understood the matters maximally. The next researches on drilling technique implementation in writing is required to evaluate or complete this study.